2012
DOI: 10.1160/th11-06-0391
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the anti-factor Xa chromogenic assay for the measurement of rivaroxaban plasma concentrations using calibrators and controls

Abstract: Rivaroxaban is an oral, direct factor Xa inhibitor. Routine coagulation monitoring is not required, but a quantitative determination of rivaroxaban concentrations might be useful in some clinical circumstances. This multicentre study assessed the suitability of the anti-factor Xa chromogenic assay for the measurement of rivaroxaban plasma concentrations (ng/ml) using rivaroxaban calibrators and controls, and the inter-laboratory precision of the measurement. Twenty-four centres in Europe and North America were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(35 citation statements)
references
References 33 publications
0
35
0
Order By: Relevance
“…Investigators found a greater degree of assay imprecision at higher rivaroxaban concentrations (800 ng/ml) in one study (45). In a multicenter study, both intra- and interlaboratory precision were satisfactory except at the lower limit of detection (20 ng/ml); use of a centrally distributed reagent reduced interlaboratory variability (46). Mathematical modeling also decreased interassay variability resulting from different sensitivities of individual reagents to rivaroxaban (40).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Investigators found a greater degree of assay imprecision at higher rivaroxaban concentrations (800 ng/ml) in one study (45). In a multicenter study, both intra- and interlaboratory precision were satisfactory except at the lower limit of detection (20 ng/ml); use of a centrally distributed reagent reduced interlaboratory variability (46). Mathematical modeling also decreased interassay variability resulting from different sensitivities of individual reagents to rivaroxaban (40).…”
Section: Resultsmentioning
confidence: 96%
“…The correlation was less robust at concentrations <100 ng/mL (49). However, Samama and colleagues demonstrated that low rivaroxaban concentrations could be measured with a modified anti-Xa test using less diluted samples (46). Investigators found a greater degree of assay imprecision at higher rivaroxaban concentrations (800 ng/ml) in one study (45).…”
Section: Resultsmentioning
confidence: 99%
“…Studies have indicated that the anti-factor Xa chromogenic method is the best test for assessing rivaroxaban exposure when used in conjunction with rivaroxaban calibrators and controls 20, if a quantitative assessment of rivaroxaban exposure is required in certain clinical situations. It should be emphasized that, although rivaroxaban affects the PT/INR, this system is not suitable for assessing the anticoagulant intensity of rivaroxaban 6,7.…”
Section: Discussionmentioning
confidence: 99%
“…The target specific inhibitors dabigatran, rivaroxaban and apixaban represent a new class of anticoagulants that can not be monitored with global coagulation tests due there is not a predictable linear relationship between laboratory value and drug concentration 49–56. Chromogenic anti-factor Xa assays have been demonstrated to have the potential for accurate measurement of plasma concentrations of the direct factor Xa inhibitors 5760. However, the threshold values of drug concentrations and the degree of prolongation that might still be assumed as safe must be defined.…”
Section: Health Outcomes and Patients’ Quality Of Lifementioning
confidence: 99%